Development of carbon-infiltrated bio-char from oil palm empty fruit bunch - Rozhan, Alya Naili; Ani, Mohd Hanafi; Mohd. Salleh, Hamzah; Akiyama, Tomohir; Purwanto, Hadi (The Iron and Steel Institute of Japan, 2015)
This paper presents a technology to utilize bio-char and bio-tar from the pyrolysis of oil palm empty fruit bunch, EFB. In this study, tar vapor from pyrolysis of EFB was infiltrated within porous bio-char and carbon deposition occurred on the pore surface by chemical vapor infiltration process. For preparation, EFB particles were made into pellets. In the first part of experiments, porous bio-char pellets were produced by slowly heating the EFB pellets in a tube furnace in argon atmosphere to terminal temperatures of 500–800°C. In the second part, the porous bio-char pellets were used as precursor for tar decomposition process to deposit carbon within the bio-char pores. Tar vapor was obtained from the pyrolysis of EFB at 400–500°C at a fast heating rate for tar decomposition to occur. The purpose of this research is to investigate the amount of carbon deposited within bio-char by this tar carbonization process as compared to carbon contents of metallurgical coke. We showed how EFB bio-char was used as the tar filter and in the process to produce carbon-infiltrated bio-char, a useful renewable energy source for ironmaking process.